Factors affecting sunflower threshing performance of a small axial flow threshing unit - Muenkaew, Pisal; Duangkhamjan, Jakraphan; Chuan-Udom, Somchai (Engineering and Applied Science Research, 2022)
The small axial flow threshing unit design for mounting on tractors tractor was necessary to study the design factors for the threshing unit to have high performance, and low cost of the machine. The objective of this research was to study the factors affecting sunflower threshing performance of a small axial flow threshing unit. Moisture content of the grain and extraneous material were 14.26% and 62.83% respectively. The grain to material other than grain ratio was 1.49 at a feed rate was 1,200 kg/h. The results showed that peg-tooth clearance had no statistically significant effect on threshing performance, but grain purity (GP) increased with decreased peg-tooth clearance. Thus, decreased peg-tooth clearance affected grain breakage, while the threshing unit required a higher specific energy consumption (SEC), but threshing performance was not affected at a statistically significant level. Furthermore, reducing peg-tooth clearance and concave clearance did not affect threshing efficiency, percentage of broken grains breakage, and power requirements, but specific energy consumption was higher while losses decreased. Optimal parameters of threshing at maximum performance resulted in losses and grain breakage of no more than 2%. Threshing efficient was not less than 95%. Therefore, a concave rod clearance of not more than 25 mm, peg-tooth clearance of the threshing unit of between 125 mm and 150 mm, concave clearance and peg-tooth clearance were not more than 10 mm is recommended to farmers who may operate this unit.